1988
DOI: 10.3109/00016488809119446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interaction between Noise and Toluene on Auditory Function in the Rat

Abstract: Rats were exposed to toluene (1000 ppm, 16 h/d, 5 d/w, 2 w), or noise (100 dB Leq, 10 h/d, 7 d/w, 4 w) or toluene followed by noise. Auditory function was tested by brainstem audiometry using a 1/3 octave filtered sine wave stimulus at the frequencies 1.6, 3.15, 6.3, 12.5 and 20.0 kHz. A high-frequency auditory impairment was observed after exposure to toluene alone and noise alone. A slight recovery was recorded 1 and 6 months after the toluene exposure. Toluene followed by noise resulted in a higher threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 10 publications
2
32
2
1
Order By: Relevance
“…Toluene ototoxicity has been discus sed previously. Evidence indicating that toluene exposure affects hearing comes mainly from studies conducted with toluene abusers (21)(22)(23)(24) and animal s (8,(27)(28)(29)(30)(31). In rats toluene interacted synergistically with noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene ototoxicity has been discus sed previously. Evidence indicating that toluene exposure affects hearing comes mainly from studies conducted with toluene abusers (21)(22)(23)(24) and animal s (8,(27)(28)(29)(30)(31). In rats toluene interacted synergistically with noise.…”
Section: Discussionmentioning
confidence: 99%
“…In the United State s at least one million workers in manufacturin g are estimated to have sustained job-related hearing impairment , and about a half million of the se work er s have moderate to severe he aring imp airment (I ). Occupation al hearing loss has long been reco gnized as a direct health effect of overexpo sur e to nois e, but only recently has expo sure to solv ent s been con sidered as a contributor to the development of hearing impairment (4)(5)(6)(7)(8)(9)(10). There is evidence wh ich suggests that noise interact' > synerg istica lly with various drugs and chemicals (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…: Experiments with rats have shown that combined exposure to noise and solvents (such as toluene, styrene, and ethylbenzene) induces synergistic adverse effects on hearing. [77][78][79][80][81] In most of these investigations, high concentrations of solvents were used for short intervals of time, conditions which do not accurately reflect occupational exposure conditions.…”
Section: Co-exposurementioning
confidence: 99%
“…A large number of studies have examined the nature of the interaction between noise and organic solvents and its impact on hearing in animal experiments. A potentiation of the auditory impairment was found in rats exposed sequentially to toluene (1000 ppm 16 hours/day, 5 days/week for 2 weeks) and noise (100 dB L eq 10 hours/day, 7 days/ week for 4 weeks) when toluene exposure preceded noise exposure [5]. A reverse exposure order resulted only in an additive effect [30].…”
Section: Animalsmentioning
confidence: 81%
“…The possible ototoxic effect of toluene was fi rst reported in rats by Pryor et al [1], and subsequent studies demonstrated hearing loss in rats after exposure to toluene [2][3][4][5][6][7][8][9][10][11], styrene [8,[12][13][14][15][16][17][18], xylene [8,9,12], ethyl benzene [19,20], trichloroethylene [8,9,[21][22][23][24], chlorobenzene [9], and n-heptane [25]. The ototoxic potency of the different solvents varies signifi cantly [9,14,26], but when rats were exposed to different combinations of organic solvents, the auditory impairment was additive with respect to the potency of the solvents under study [9].…”
Section: Introductionmentioning
confidence: 99%